2011
DOI: 10.3899/jrheum.100752
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of Delayed Addition of Adalimumab to Methotrexate Therapy Over 5 Years in Patients with Rheumatoid Arthritis

Abstract: Objective.This Year 5 analysis of an open-label extension (OLE) study assessed radiographic progression, clinical efficacy, and safety of adalimumab with concomitant methotrexate (MTX) for patients with active rheumatoid arthritis.Methods.In a double-blind study (DE019, NCT00195702), inadequate responders to MTX were randomized to MTX plus either adalimumab 40 mg eow, adalimumab 20 mg weekly, or placebo for 52 weeks. Eligible patients entered an ongoing OLE and received adalimumab 40 mg eow plus MTX. Longterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…The proportions of patients who remained in the trials – and consequently were persistent to golimumab treatment – after 256 weeks were 65.8% in GO-BEFORE and 70.5% in GO-FORWARD. For etanercept, adalimumab, and certolizumab pegol, the five-year persistence rates from extension studies of RCTs in TNFi-naive RA patients were 56%,46 49%,47 and 55%,48 respectively. The persistence estimate with the longest follow-up (36 months) from clinical practice in biologic-naive RA patients was 60% 35.…”
Section: Resultsmentioning
confidence: 99%
“…The proportions of patients who remained in the trials – and consequently were persistent to golimumab treatment – after 256 weeks were 65.8% in GO-BEFORE and 70.5% in GO-FORWARD. For etanercept, adalimumab, and certolizumab pegol, the five-year persistence rates from extension studies of RCTs in TNFi-naive RA patients were 56%,46 49%,47 and 55%,48 respectively. The persistence estimate with the longest follow-up (36 months) from clinical practice in biologic-naive RA patients was 60% 35.…”
Section: Resultsmentioning
confidence: 99%
“…The methodology and primary results for the 1-year, double-blind phase of DE019, a randomized, placebo-controlled trial of adalimumab in patients with moderate to severe RA who demonstrated an inadequate response to MTX, have been published 6 , as have results from the first 4 years of the open-label extension 17 . The study protocol and informed consent forms were approved by the local institutional review boards (USA) or research committees (Canada) at each participating site.…”
Section: Methodsmentioning
confidence: 99%
“…They had accrued significant amounts of radiographic damage (mean mTSS was 51), with low function (mean HAQ-DI was 1.4; Table 1). Baseline characteristics for all randomized patients (n = 619) and patients who received at least 1 injection of adalimumab during blinded or open-label therapy (n = 553; safety population) have been described 6,17 . Characteristics were generally similar between the 10-year radiographic completers and the overall intent-to-treat population, with the exception that the radiographic completers appeared to represent a younger subset of the overall randomized population.…”
Section: Patientsmentioning
confidence: 99%
“…Two studies were included in this post hoc analysis; details of the methods, primary results, and 5‐ and 10‐year findings have been previously described (). DE019 was a 1‐year, double‐blind, multicenter, randomized placebo‐controlled trial in patients with longstanding RA, followed by a 9‐year, open‐label extension period.…”
Section: Methodsmentioning
confidence: 99%